Bilateral Iliosacral and Transsacral Screws Are Biomechanically Favorable and Reduce the Risk for Fracture Progression in Fragility Fractures of the Pelvis—A Finite Element Analysis - Moritz F. Lodde; Matthias Klimek; Elmar Herbst; Christian Peez; Oliver Riesenbeck; Michael J. Raschke; Steffen Roßlenbroich (Bioengineering)
(1) Background: The incidence of fragility fractures of the pelvis (FFP) has increased significantly over the past decades. Unilateral non-displaced fractures, defined as FFP II, are the most common type of fracture. When conservative treatment fails, surgical treatment is indicated. We hypothesize that the use of bilateral SI screws (BSIs) or a transsacral screw (TSI) is superior compared to a unilateral screw (USI) because of a significant reduction in the risk of adjacent fractures and a reduction in fracture progression. (2) Methods: A finite element model of a female pelvic ring was constructed. The ligaments were simulated as tension springs. The load was applied through the sacrum with the pelvis fixed to both acetabula. An FFP IIc was simulated and fixed with either a USI or BSI or TSI. The models were analyzed for a quantitative statement of stress and fracture dislocation. (3) Results: The BSI and TSI resulted in less dislocation compared to the USI. The stress distribution on both sides of the sacrum was favorable in the BSI and TSI groups. The BSI resulted in a higher rotational stability compared to the TSI. (4) Conclusions: The use of either a BSI or TSI for fixation of unilateral FFP is biomechanically favorable compared to the use of a USI. In addition, the use of a BSI or TSI reduces the stress on the contralateral uninjured side of the sacrum. This may reduce the risk of an adjacent fracture or fracture progression.